BAHAN AJAR DIGITAL BERBASIS MICROSOFT SWAY PADA MATA PELAJARAN PPKN - Aryanti Dwi Untari; Muhammad Asmawi; Pungky Enjelita (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2023)
Abstract This study aims to determine how the process of developing Microsoft Swaybased digital teaching materials in student learning process in Civics subjects in class XI IPA MA Al-Khairiyah Pipitan. This study is used research and development methods. The development model in this study is used the ADDIE method (these are analysis, design, development, implementation, evaluation). Data collection techniques are used observation, interviews, documentation and questionnaires. The results of this study are digital teaching materials based on Microsoft Sway which are very feasible to use. Feasibility obtained from material expert validation, media expert validation and learning expert validation stated that it was very feasible with an average percentage of 93.31% of material expert assessment, 91.96% average percentage of media expert assessment, average percentage 98.21% learning expert assessment. The teacher's response as a user has an average percentage of 96.42% assessment and student responses to the developed teaching materials have an average percentage of 94.06% assessment. So it can be concluded that digital teaching materials based on Microsoft Sway in strengthening the unity and integrity of the nation within the Unitary State of the Republic of Indonesia are very suitable to be used as teaching materials in the learning process.